Genome analysis of two virulent Streptococcus thermophilus phages isolated in Argentina - Guglielmotti, Daniela Marta (2009)
Two Streptococcus thermophilus phages (ALQ13.2 and Abc2) were previously isolated from breakdowns of cheese manufacture in Argentina. Complete nucleotide sequence analysis indicated that both phages contained linear double-stranded DNA: 35,525 bp in length for the pac-type phage ALQ13.2 and 34,882 bp for the cos-type phage Abc2. Forty-four and 48 open reading frames (ORF) were identified for ALQ13.2 and Abc2, respectively. Comparative genomic analysis showed that these isolates shared many similarities with the eight previously studied cos- and pac-phages infecting different S. thermophilus strains. In particular, part of the Abc2 genome was highly similar to a region of phage 7201, which was thought to be unique to this latter phage. Protein analysis of the pac-phage ALQ13.2 using SDS polyacrylamide gel electrophoresis (SDSPAGE) identified three major proteins and seven minor proteins. Parallel structural proteome analysis of Abc2 revealed seven protein bands, two of which were related to major structural proteins, as expected for a cos-type phage. Similarities to other S. thermophilus phages suggest that the streptococcal phage diversity is not extensive in worldwide dairy factories possibly because related high-performing bacterial strains are used in starter cultures.